ANXIETY DISORDER AS REFLECTED IN JAY AHSER’S THIRTEEN REASONS WHY MAIN CHARACTER - Sualang, Jeansly; Mogea, Tini; Maukar, Merlin M. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to find out the kinds of anxiety and its causes experienced by the main character Hannah Baker in the novel Thirteen Reasons Why. He was badly treated by his friends, teachers and parents. All bad things happened to Hannah then bring anxiety in Hannah Baker's life. The method used of this research is qualitative with psychological approach by Sigmund Freud. The data that are taken from the monologue and dialogue with the other characters in the novel. The study using the psychological approach of Sigmund Freud. The primary source is the 2007 book Thirteen Reasons Why by Jay Asher, while secondary sources include various related publications and online resources that provide credence to the subject. The result of the study showed there are three kinds of anxiety. The first is neurotic anxiety, when Hannah scares to share her phone number with her friend. The next is realistic anxiety, when a Hannah’s friend is staring at her in the house and scares her. The last is moral anxiety that is when she doesn't join the funeral of a driver who makes herself scared by what others think about her. The author also found causes of such anxiety: environment, frustration, threat, gender and fear. From all the data found in the novel, it proves that Hannah Baker suffered anxiety and eventually died of suicide.